Beta-catenin inhibits bovine parainfluenza virus type 3 replication via innate immunity pathway - Xinying Du; Wenqi He; Hongbin He; Hongmei Wang (BMC Veterinary Research, 2020)
Abstract Background Bovine parainfluenza virus type 3 (BPIV3) is one of the important viral respiratory agents associated with the bovine respiratory disease complex (BRDC) in cattle. Previous study has demonstrated that infection of BPIV3 causes innate immune response within the host cell. β-catenin is a key component of the Wnt/β-catenin signal pathway which is involved in the regulation of interferon-beta (IFN-β) transcription. Some viruses can activate while others can inhibit the Wnt/β-catenin signaling pathway. However, the role of β-catenin in BPIV3 infection remains unclear. Results Here we found that the expression of β-catenin mRNA was up-regulated and β-catenin protein was down-regulated after BPIV3 infection in MDBK cells. Moreover, it was confirmed that overexpression of β-catenin suppressed BPIV3 replication and knockdown of β-catenin promoted viral replication, suggesting that β-catenin inhibits BPIV3 replication. Furthermore, IFN-β signal pathway and virus titer analysis using the GSK3β inhibitor (LiCl) revealed that Wnt/β-catenin can serve as a mechanism to suppress virus replication in infected cells. The results indicated that LiCl promoted the expression and accumulation in the nucleus of β-catenin, which further promoted the expression of IFN-β and OSA1 and suppressed BPIV3 replication. Most importantly, BPIV3 down-regulating β-catenin protein expression was due to degradation of GSK3β mediated proteasome pathway. Conclusions In summary, we discovered the relationship between β-catenin and BPIV3 replication. These results provided further insight into the study of BPIV3 pathogenesis.